TAKHRIJ HADIST: LANGKAH AWAL PENELITIAN HADIST - Jon Pamil (An-Nida', 2012)
This article is aimed to describe about “takhrij hadis”,that includes the meaning, advantages and methods. From relevant references known that “takhrij hadis” is an effort to find “matan” and “sanad” of hadis, completely from original references. It is clear that the quality of hadis is even known by collector directly through researches. The advantages of takhrij hadis are: (a) collecting variety of “sanad” of the “hadis” (b) collecting variety of “matan” of the “hadis”. They are the inportant materials for the research. To implement takhrij hadis can be used several methods. (1) takhrij from spelling in matan of hadis, (2) takhrij from first spelling of the hadis, (3) takjhrij from first collector (4) takhrij from the topic of hadis. Besides manual implementation, takhrij hadis can use the technology such as computer by using compact disc (CD) installed with takhrij hadis program